The Anticarceral Promise of Deregulating Motherhood and Decriminalizing Substance Use - Garcia-Hallett, Janet; Begum, Popy (Journal of the Motherhood Initiative for Research and Community Involvement, 2022)
Carceral systems in the United States (US) criminalize individuals who engage in substance use and marginalize them under the guise of public safety. In particular, the US war on drugs has disproportionately affected incarceration rates of eco-nomically disadvantaged Black women—a majority of whom are mothers of children under the age of eighteen. Within carceral systems, social workers have dual and fluid roles as both social service providers and compliance managers who enforce the carceral logics that disadvantage Black mothers. This article asserts that social practitioners, especially social workers, should advocate for anticarceral efforts and engage in community-based practices that reduce harm, remove stigma, and replace perceived criminality with dignity.